Decision-making process in game sports: what do top-level players think of current research? - Magnaguagno, Lukas; Beck, Damian (Frontiers in Sports and Active Living, 2025)
IntroductionExcellent performance in game sports is largely determined by a functional decision-making process which integrates different perceptual-cognitive skills. This paper aims to bridge empirical and practical knowledge by exploring top-level players' subjective experiences in decision making.MethodsA semi-structured interview guide was developed and informed by existing decision-making literature including three categories (i.e., gaze behavior, information integration, and decision determinants). Each Switzerland's most successful male and female player from five different game sports (i.e., beach volleyball, floorball, handball, ice hockey, and soccer) participated in single interviews, focusing different aspects within each of the three categories. Verbal data were analyzed using a deductive thematic analysis after which top-level players' perspective was compared against the selected theoretical concepts and empirical findings.ResultsThe data analysis showed that top-level players use gaze anchor and foveal spot for peripheral vision, anticipate based on a weighted combination of kinematic and different contextual information, and decide predominantly intuitively by applying if-then automatism.DiscussionThe present findings reflect well-examined factors of the decision-making process and uncover specifics relevant to top-level players but underrepresented in the literature such as decisional relevance when using peripheral vision, or tactical strategies influencing decisions. Therefore, our results provide player-perspective information underlying the decision-making process in complex game situations as well as valuable recommendations for applied practices.